Effects of urbanization and global climate change on regional climate in the Pearl River Delta and thermal comfort implications. (14th February 2019) - Wang, Yongli; Chan, Allen; Lau, Gabriel Ngar‐Cheung; Li, Qingxiang; Yang, Yuanjian; Yim, Steve Hung Lam
Abstract : Urbanization and climate change are affecting regional climate; therefore, thermal comfort should be fully understood, especially from a public health perspective. We applied a climate model driven by a combination of land‐cover development and two representative concentration pathways (RCP4.5 and RCP8.5) to predict composite climatic adjustments in the Pearl River Delta (PRD) in China. Our findings showed that a 10% increase in urban land cover can cause a 0.11 K increase in surface temperature in PRD, and urban temperature will rise by 0.15–0.21 K because of global climate change alone. We found that urbanization has marginal effects on thermal comfort despite increasing surface temperature in PRD. Moreover, global climate change will increase the frequency at which temperatures exceed critical temperatures reported in the literature and the extreme heat stress level (95th percentile of baseline year). Our findings offer a scientific basis for understanding heat‐related health risk and climate change adaptation in urban areas. Abstract : Diurnal temperature range (DTR) in existing urban areas decreases due to urbanization that is consistent with literature, but DTR in newly urbanized areas increases that has not yet been reported before. Urbanization has marginal impacts on thermal comfort even though surface air temperature is increased. Climate change will increase frequency of exceedance of critical temperature reported in literature and extreme thermal comfort level.